Representasi Penerapan Hukum Islam Dalam Kehidupan Perempuan Iran: Analisis Komik Persepolis - Salma Fitriyani; Fauzaan Taufiqurrahman; Sarah Novian; Yusthalya Nurfitri; Tenny Sudjatnika (Indo Publishing, 2026)
This study discusses the representation of Islamic law in the lives of Iranian women through an analysis of Marjane Satrapi's autobiographical comic Persepolis. The background of this study stems from the socio-political changes following the 1979 Islamic Revolution in Iran, which made Islamic law the basis of state policy through the Wilāyat al-Faqīh system. This policy had a significant impact on the regulation of women's bodies, public spaces, and identities, particularly through dress codes, moral control, and social restrictions. This study uses a descriptive qualitative approach with literature study and visual text analysis methods. Persepolis is analyzed as a cultural text using gender theory, Stuart Hall's theory of representation, and contemporary fiqh and maqāṣid al-syarī‘ah perspectives. The results show that Persepolis represents the application of Islamic law in Iran more as an instrument of patriarchal political power than as a contextual and welfare-oriented practice of sharia. This comic depicts how women's bodies and lives become objects of state surveillance through the enforcement of the hijab, the segregation of social spaces, and the criminalization of behavior deemed deviant from the state's official morality. These findings reveal a gap between the normative principles of Islamic law, which emphasize justice and human dignity, and the state's repressive legal practices against women. Thus, Persepolis serves as a cultural critique of the rigid application of Islamic law and its insensitivity to gender experiences.